The identification of severity ranges for the Edinburgh Postnatal Depression Scale. (26th May 2016) - McCabe-Beane, Jennifer E.; Segre, Lisa S.; Perkhounkova, Yelena; Stuart, Scott; O'Hara, Michael W.
Abstract: Objective : The present study established severity cut-off scores for the Edinburgh Postnatal Depression Scale (EPDS) based on a widely used depression symptom severity measure, the Beck Depression Inventory (BDI). Background : The EPDS is a widely used screening tool to identify clinically significant levels of depression in postpartum women. Traditionally, an EPDS cut-off score is used to identify probable depression. This dichotomisation of postpartum women into depressed vs. non-depressed groups fails to account for valuable information regarding the variability in symptom severity among those in the depressed group. The identification of depression severity ranges (e.g. mild, moderate or severe) for the EPDS would provide incremental information regarding level of depression, which in turn, could inform treatment referrals. Methods : A sample of 1516 postpartum women completed the EPDS and the BDI. Equipercentile linking was used to develop concordance between EPDS and BDI scores, and severity ranges were established by identifying EPDS scores that corresponded to established severity ranges on the BDI. Results : The following severity ranges were established for the EPDS: none or minimal depression (0–6), mild depression (7–13), moderate depression (14–19), and severe depression (19–30). Conclusion : Postpartum women experience a wide range of depression severity. The establishment of severity ranges for EPDS scores may guide treatment referrals. Although the study sample size was large, only a limited number of women scored in the severe range of depression symptoms. Replication in a larger sample of depressed women is an important direction for future research.